Appraisal Analysis of Cinta Laura’s Interview with Asian Boss about Woman Rights and Children Education - Avissa, Belinda Leona; Mulatsih, Sri (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2021)
Appraisal is the system which used to identify the writer’s or speaker’s views, opinions, or feelings toward something, somebody, or some issue. Appraisal is also used to reflect the value of someone or something (Martin, J.R., 2003). Moreover, appraisal also used to construct and maintain the relationship between the writer or speaker and the reader or listener. Analysis on appraisal not only can be done on written texts, but also on the utterances, such as an interview or a podcast, which possibly also include someone’s opinion. One of them is the interview between Asian Boss, an independent Korean media company and Cinta Laura Kiehl, an Indonesian actress, influencer, and children’s also women’s right activist. Hosted by Marie, Cinta Laura shared her views and feelings toward bullying, children and women abuses also educations. The research aims: (1) to identify the interacting domains occurred the most during the interview; (2) to identify the appraising items occurred during the interview; and (3) to identify the functions of appraising items in the interview. The research used Martin and Rose framework and supported by other theories such as Martin and White’s. The research used qualitative-descriptive approach and documentation data collection method. The researcher found that the interview between Cinta Laura and the Asian Boss’ host, Marie mostly consisted of positive judgments which refers to speakers attitude toward someone or something. The function of appraising items mostly used to evaluate someone or something and to express feelings toward someone or something.